Comparing the effectiveness of acceptance and commitment-based therapy and cognitive behavioral therapy on body image concerns of overweight women - Rashidi Zafar, Maryam; Bashardost Tajali, Fariba; Sharifi, Nastaran (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to determine and compare the effectiveness of cognitive-behavioral therapy with acceptance and commitment-based therapy on body image concerns in overweight women. Method: The research design was a quasi-experimental pre-test-post-test type with a follow-up phase in three experimental and control groups. The statistical population of the research consisted of all overweight women (body mass index between 25 and 29.9) of Varamin city in the year 2021, 60 of whom were selected as a statistical sample using the available sampling method and divided into three experimental and control groups. First, all three groups were evaluated with the body image concern questionnaire of Littleton et al. (2005). The experimental group of cognitive behavioral therapy using the treatment protocol of Pimentera et al. (2017) and the experimental group of treatment based on acceptance of commitment using the treatment protocol of Ciarrochi, Bailey and Harris (2005) were subjected to intervention for eight sessions of 90 minutes. Collected data were analyzed using variance of repeated measures. Results: The results showed that cognitive-behavioral therapy and therapy based on acceptance and commitment were effective on body image concerns (F=28.21, P=0.001) in overweight women and this effect was stable in the follow-up phase. Was. Also, the results of the follow-up test showed that there is no difference between the two treatment methods and both interventions were effective in reducing body image concerns. Conclusion: Considering the effectiveness of cognitive-behavioral therapy and therapy based on acceptance and commitment on body image concerns in overweight women, these two interventions can be effective methods for body image concerns in overweight people.